PARTICIPATION MANAGEMENT PRACTICES EFFECT ON COMMITMENT: THE SAMPLE OF IRAQ ELECTRICITY INDUSTRY - Samer Hammad Assi; Asst. Prof. Dr. Emine Sener; Prof. Dr. Musa Ozata (Scholar Express Journals, 2023)
In this study, the effect of participative management practices on organisational commitment in the Iraqi electricity sector is examined. The population of the research, which is within the scope of relational screening model, is the employees of the electricity sector in Iraq. The study group of the research consists of 145 people who can be reached among the employees working in electricity production and electricity distribution companies in Baghdad Province of Iraq. The data of the research were obtained by questionnaire method. In this direction, Iraqi Electricity Sector Employee Questionnaire, Employee General Information Questionnaire, Participative Management Scale and Organisational Commitment Scale were applied to the participants and the data obtained were analysed with SPSS statistical package programme. At the end of the study, the following findings were obtained. organisational commitment scale showed differences according to sociodemographic data. Emotional commitment sub-dimension differs according to sociodemographic data. Continuance commitment subdimension differed according to sociodemogrophic data. normative commitment sub-dimension differed according to sociodemogrophic data. C2 scale differs according to sociodemogrophic data. C3 scale differs according to sociodemogrophic data. Positive aspects and advantages of Iraqi electricity sector differ according to sociodemogrophic data. The negative aspects and disadvantages of the Iraqi electricity sector differ according to sociodemogrophic data
Keywords: Management; Participatory Management; Organizational Commitment